At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's solve the system of equations using the elimination method step-by-step.
Given equations:
[tex]\[ \begin{cases} 3x + y = 5 \\ 2x - 2y = -2 \end{cases} \][/tex]
1. Simplify the second equation:
Divide the second equation by 2 to simplify it:
[tex]\[ \frac{2x - 2y}{2} = \frac{-2}{2} \][/tex]
Simplifying, we get:
[tex]\[ x - y = -1 \][/tex]
2. Rewrite the system:
Now, we have a simpler system of equations:
[tex]\[ \begin{cases} 3x + y = 5 \\ x - y = -1 \end{cases} \][/tex]
3. Add the equations to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} &3x + y + x - y = 5 + (-1) \\ &4x = 4 \\ &x = 1 \end{aligned} \][/tex]
4. Substitute [tex]\( x = 1 \)[/tex] back into the simpler equation [tex]\( x - y = -1 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} 1 - y &= -1 \\ -y &= -1 - 1 \\ -y &= -2 \\ y &= 2 \end{aligned} \][/tex]
Hence, the solution to the system of equations is:
[tex]\[ (x, y) = (1, 2) \][/tex]
Therefore, the correct answer is:
[tex]\[ (1, 2) \][/tex]
Given equations:
[tex]\[ \begin{cases} 3x + y = 5 \\ 2x - 2y = -2 \end{cases} \][/tex]
1. Simplify the second equation:
Divide the second equation by 2 to simplify it:
[tex]\[ \frac{2x - 2y}{2} = \frac{-2}{2} \][/tex]
Simplifying, we get:
[tex]\[ x - y = -1 \][/tex]
2. Rewrite the system:
Now, we have a simpler system of equations:
[tex]\[ \begin{cases} 3x + y = 5 \\ x - y = -1 \end{cases} \][/tex]
3. Add the equations to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} &3x + y + x - y = 5 + (-1) \\ &4x = 4 \\ &x = 1 \end{aligned} \][/tex]
4. Substitute [tex]\( x = 1 \)[/tex] back into the simpler equation [tex]\( x - y = -1 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} 1 - y &= -1 \\ -y &= -1 - 1 \\ -y &= -2 \\ y &= 2 \end{aligned} \][/tex]
Hence, the solution to the system of equations is:
[tex]\[ (x, y) = (1, 2) \][/tex]
Therefore, the correct answer is:
[tex]\[ (1, 2) \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.